Peranan Penting Teknologi Digital dalam Pelestarian Karya Sastra pada Generasi Z di Indonesia: The Important Role of Digital Technology in Preserving Literary Works Among Generation Z in Indonesia - Mardi, Melia; Putri, Desmimi Eka; Syofiani, Syofiani; Morelent, Yetty (Information Technology and Science(ITScience), 2025)
The development of digital technology has had a major impact on various aspects of life, including in the world of education and literature. One real change is the shift in the way the younger generation, especially Generation Z, accesses and appreciates literary works. This generation grew up in a fast-paced, visual, and interactive digital environment, so they are more interested in digital media, such as short videos, podcasts, and social media than conventional literary texts. This has led to declining interest in classic and contemporary literary works. Therefore, it is important to explore how digital technology can be utilised to preserve literature based on the characteristics of Generation Z. This study uses a literature study and observation approach. Literature studies are conducted by reviewing scientific articles, rereviewing reports, and current data related to digital literacy and literature. Observations are made on digital platforms such as Wattpad, YouTube, podcasts, and social media containing literary content. The study results show that digitising literary works, audio-visual format presentation, and active social media involvement can increase the younger generation's interest in and appreciation of literature. Digital technology also plays a role in expanding public access to literary works across time and regions. With a contextual and creative approach, digital technology is a distribution medium and a strategic instrument in preserving, revitalising, and inheriting works.